SOCIO ECONOMIC FACTORS, PERSONAL HABITS AND OCCURANCE OF ORAL PREMALIGNANT SYMPTOMS AMONG FISHER FOLK - Sofi Cherian and L. Prema (REVIEW OF SOCIAL SCIENCES, 2014)
The fishermen population is recognized as socially and economically vulnerable. The present study was conducted among fisher folk from coastal area of Thiruvananthapuram, Kerala. Three hundred respondents of both sexes in the age group of 40 to 60 years formed the study group. It was observed that risk of oral premalignant symptoms increased with increase in age, illiteracy and low percapita income. Joint families and large sized families with more number of children were higher among respondents showing symptoms. Among the health related personal habits tobacco chewing was found to be the most important risk factor.